2007
DOI: 10.1038/sj.npp.1301329
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Effects of Three Dopamine Agonists with Different Dyskinetogenic Potential and Receptor Selectivity Using Pharmacological Functional Magnetic Resonance Imaging

Abstract: The mechanisms underlying dopamine agonist-induced dyskinesia in Parkinson's disease remain poorly understood. Similar to patients, rats with severe nigrostriatal degeneration induced by 6-hydroxydopamine are more likely to show dyskinesia during chronic treatment with unselective dopamine receptor agonists than with D2 agonists, suggesting that D1 receptor stimulation alone or in conjunction with D2 receptor stimulation increases the chances of experiencing dyskinesia. As a first step towards disclosing drug-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 48 publications
(94 reference statements)
1
40
0
Order By: Relevance
“…We previously showed that D 1 agonists produce large positive CBV changes in the striatum, while D 2 /D 3 agonists (norpropylapomorphine, quinpirole and 7-OHDPAT) produce negative CBV changes in rats (Chen et al, 2005;Choi et al, 2006). Using BOLD a recent study in dyskinetic rodents has reported similar positive changes with D 1 (or non-selective) agonists (Delfino et al, 2007) while D 2 did not produce positive BOLD changes. Thus, since the CBV change observed in the dyskinetic animals is positive it is unlikely due to lack of specificity of the 7-OHDPAT for D 3 over D 2 receptors as the D 2 receptor activation should produce a negative CBV change.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…We previously showed that D 1 agonists produce large positive CBV changes in the striatum, while D 2 /D 3 agonists (norpropylapomorphine, quinpirole and 7-OHDPAT) produce negative CBV changes in rats (Chen et al, 2005;Choi et al, 2006). Using BOLD a recent study in dyskinetic rodents has reported similar positive changes with D 1 (or non-selective) agonists (Delfino et al, 2007) while D 2 did not produce positive BOLD changes. Thus, since the CBV change observed in the dyskinetic animals is positive it is unlikely due to lack of specificity of the 7-OHDPAT for D 3 over D 2 receptors as the D 2 receptor activation should produce a negative CBV change.…”
mentioning
confidence: 69%
“…These data clearly indicate a D 3 preference of 7-OHDPAT in vivo. Moreover, in another recent study (Delfino et al, 2007), quinpirole (a D 2 preferring agonist) did not increase BOLD signal, or induce sensitization -strongly arguing against a sensitization of D 2 receptors in dyskinetic rats. Lastly, we have some preliminary evidence using the selective D 3 antagonist SB277011 supporting D 3 involvement in the rCBV change observed in the striatum of dyskinetic animals (Sanchez-Pernaute and Jenkins, unpublished observation) as the aberrant activation reported here was suppressed on the ipsilateral side by the D 3 antagonist, while 6-OHDA-lesioned rats showed bilateral medial activation similar to what we have shown previously with eticlopride, a D 3 /D 2 antagonist (Chen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, amphetamines are known to increase DA levels as well as alter the kinetics of other neurochemicals that affect the regional CBV [34], whereas CBV responses may differ from BOLD responses [35]. Different DARs exert different effects on the hemodynamic signals [30]; stimulation of D1 receptors (D1Rs) increases CBV and BOLD responses [30,32], whereas blocking these receptors decreases them [30,36]. The activation and deactivation of D2 receptors (D2Rs) produce opposite effects [37].…”
Section: Functional Imagingmentioning
confidence: 97%
“…The effects of DA on the hemodynamic signals have been extensively addressed using different pharmacological agents in rats and monkeys [29][30][31][32][33]. For instance, amphetamines decreased CBV responses in occipital regions [33].…”
Section: Functional Imagingmentioning
confidence: 99%
“…L-DOPA-induced dyskinesia (LID) is causally linked with hyperstimulation of dopamine D1 receptors (D1R) located on direct pathway medium spiny neurons (MSNs) of the severely denervated striatum (1)(2)(3). In the dopamine-depleted striatum, L-DOPA activates a cAMP-dependent signalling cascade via PKA activation (4,5), resulting in abnormally increased phosphorylation of DARPP-32 and activation of the Ras/ERK signalling pathway in the same neurons (1,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%